Measuring National Income and Growth in Resource-Rich, Income-Poor Countries - Hamilton, Kirk; Ley, Eduardo (World Bank, Washington, DC, 2012)
In the decade leading to the recent commodity boom, which peaked in 2007-08, several resource-rich, low-income countries displayed high rates of gross domestic product (GDP) growth while social indicators did not improve significantly. It is well known that, in itself, the widely tracked GDP may not be the most relevant summary of aggregate economic performance in all places at all times. This note suggests that for countries with significant exhaustible natural resources and important foreign-investor presence, adjusted net national income (aNNI), can usefully complement GDP to assess economic progress.